Single Coronary Artery with Anomalous Rising of the Right Coronary Artery: A Rare Coronary Anomaly Diagnosed by 256-Multidetector Computed Tomography. (26th October 2011) - Gitsioudis, Gitsios; Giannitsis, Evangelos; Hosch, Waldemar; Kauczor, Hans U.; Katus, Hugo A.; Korosoglou, Grigorios
Abstract : Herein we report the diagnostic potential of cardiac computed tomography (cCT) to delineate the origin and course of an anomalous right coronary artery (RCA) originating from the midpart of the left anterior descended artery (LAD) in an adult with no other form of congenital heart disease. The patient was referred to our institution due to exertional dyspnea and suspected coronary artery disease. The patient underwent X-ray coronary angiography, and no high grade lesions were observed in the left coronary vessels. In the course of the mid-left-anterior-descending artery (LAD), an anomalous side branch coursing away from the left circumflex coronary artery (LCX) was observed, while a right coronary ostium could not be depicted. cCT confirmed the absence of a right coronary ostium, and the vessel originating from the mid LAD was identified as an anomalous RCA, which coursed anterior of the aorta and the pulmonary trunk.